2017
DOI: 10.1002/cbic.201700105
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of the Lipophilic Antioxidant Ferrostatin‐1

Abstract: Ferrostatin-1 (Fer-1) is a lipophilic antioxidant that effectively blocks ferroptosis, a distinct non-apoptotic form of cell death caused by lipid peroxidation. During many infections, both pathogens and host cells are subjected to oxidative stress, but the occurrence of ferroptosis had not been investigated. We examined ferroptosis in macrophages infected with the pathogenic yeast Histoplasma capsulatum. Unexpectedly, Fer-1 not only reduced the death of macrophages infected in vitro, but inhibited the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…S6). This finding is consistent with previous reports showing that Fer-1 treatment reduces macrophage cell death during Histoplasma capsulatum infection 66 . Increased BMDM survival was associated with increased C. albicans killing (Fig.…”
Section: Ferroptotic Cell Death Exerts Inflammation and Promotes Disease Severity During Candidiasissupporting
confidence: 94%
“…S6). This finding is consistent with previous reports showing that Fer-1 treatment reduces macrophage cell death during Histoplasma capsulatum infection 66 . Increased BMDM survival was associated with increased C. albicans killing (Fig.…”
Section: Ferroptotic Cell Death Exerts Inflammation and Promotes Disease Severity During Candidiasissupporting
confidence: 94%
“…Further detailed studies of ferroptosis pathway components and regulators may uncover a possible ancient origin and role of ferroptosis in archaea, bacteria, and fungi or their participation in nondeath mechanisms. These studies have to be performed carefully, as use of only a few characteristic ferroptosis inhibitors may yield misleading results, as illustrated by a study on macrophages infected with the pathogenic yeast Histoplasma capsulatum (Horwath et al 2017). It was found that a prototypical ferroptosis inhibitor, ferrostatin-1, reduced the death of macrophages, implying a possible ferroptotic mechanism.…”
Section: Bacteria Archaea and Fungimentioning
confidence: 99%
“…However, we need to pay more attention to the direct inhibitory effect of the regulator on pathogens. One study pointed out that Fer-1, a commonly used ferroptosis-inhibiting agent, reduced growth of C. neoformans in the YNB media by >95% ( 116 ). Hence, when designing an experiment, we should be able to regulate ferroptosis through multiple pathways.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Similarly, another study discovered that macrophages infected with Histoplasma capsulatum , an environmentally-acquired fungal pathogen, can also lead to increased intracellular oxidation products, and eventually cell death ( 116 ). Despite the fact that the ferroptosis inhibitor Fer-1 can reduce the cell death caused by H. capsulatum infection, further experiments have validated that the mechanism decreases fungal ergosterol synthesis, instead of inhibiting ferroptosis ( 116 ). Consequently, upon exploring the relationship between ferroptotic cell death and pathogenic mechanism of pathogens, attention needs to be paid to ferroptosis inhibitors, especially Fer-1, which may have a direct inhibitory effect on pathogens.…”
Section: Ferroptosis and Infectious Diseasesmentioning
confidence: 99%